Individualized 3D printed navigation template-assisted atlantoaxial pedicle screws vs. free-hand screws for the treatment of upper cervical fractures - Niu, Guoqi; Cheng, Jiawei; Liu, Lutan; Li, Chao; Zhou, Gong; Chen, Hui; Liu, Tao; Nie, Hu; Sun, Zheng; Jiang, Weili; Zhou, Qiankun; Zhao, Baoyin; et al. (Frontiers in Surgery, 2022)
Abstract Objective: To compare the efficacy and safety of freehand atlantoaxial pedicle screws against custom 3D printed navigation template screws in the treatment of upper cervical fractures. Methods: In our institution from 2010 to 2020, a retrospective cohort analysis of 23 patients with upper cervical fractures was done. These patients were separated into two groups, Group A (N=12), which received customized 3D printed navigation template assisted screws with virtual reality techniques, and Group B (N=11), which received freehand screws assisted by intraoperative fluoroscopy. Every patient was monitored for more than one year. The two groups were contrasted in terms of screw implant accuracy, cervical spine JOA (Japanese Orthopaedic Association) score, ASIA (American Spinal Injury Association) score, VAS (Visual Analogue Scale) score, surgical time, fluoroscopy times, and intraoperative blood loss. Result: 88 atlantoaxial pedicle screws in all, 46 in group A and 42 in group B, were implanted. In group A, the screw insertion accuracy rate was 95.7%, compared to 80.0% in group B (P < 0.05). Shorter surgery times, less blood loss, fewer fluoroscopies, a higher short-term JOA score, and overt pain reduction (P<0.05) were all observed in group A compared to group B. However, there was no discernible difference between the two groups' VAS scores, long-term JOA scores, or Asia scores (sensory and motor) at the most recent follow-up. Conclusion: Individualized 3D printed guide leads to significant improvement in the screw safety, efficacy, and accuracy, which may be a promising strategy for the treatment of upper cervical fractures.